(untitled) (Derna Academy Journal for Applied Sciences, 2025)
The application of sustainable environmental design principles represents a pivotal architectural approach, particularly in hot-humid climate zones such as Derna, Libya. This strategy seeks to achieve thermal comfort for housing occupants by harnessing natural energy resources and minimizing reliance on conventional energy systems. Among the most prominent features of traditional Derna architecture is the central courtyard, which plays a pivotal role in enhancing natural ventilation and daylighting, and ensuring privacy. This study employs a dual-method approach: a descriptive method to explore the concepts of sustainable environmental design, and a comparative method to examine key differences between traditional and modern residential architecture in Derna. The study aims to highlight the potential of environmentally and economically sustainable practices, and to evaluate the courtyard’s effectiveness as a design element integrating environmental and social needs. The findings demonstrate that traditional dwellings in Derna effectively employed intelligent environmental solutions such as thermally responsive building envelopes, strategically oriented openings, integration of green spaces, and the use of locally appropriate materials. Conversely, modern dwellings lacked these strategies, resulting in higher energy consumption and reduced quality of life. The study recommends reintegrating traditional elements, particularly the inner courtyard, into contemporary designs to create sustainable residential environments that align with local climatic and social characteristics